159k views
0 votes
Rewrite the function f(x)=3(x+1)^2-2 in the form f(x)=ax^2+bx+c

im so stuck on these problems thanks so much for the help

2 Answers

5 votes

Explanation:

f(x)=3(x+1)^2-2

= 3 [x^2 + 2x + 1 ] -2

=3x^2 + 6x +3-2

=3x^2 + 6x + 1

f(x)=ax^2+bx+c

ax^2+bx+c = 3x^2 + 6x + 1

a = 3

b = 6

c = 1

User Gaurav Shah
by
6.0k points
3 votes

Answer:

f(x) = 3x² + 6x + 1

General Formulas and Concepts:

  • Order of Operations: BPEMDAS
  • Expand by FOIL (First Outside Inside Last)
  • Standard Form: f(x) = ax² + bx + c
  • Vertex Form: f(x) = a(bx + c)² + d

Explanation:

Step 1: Define function

f(x) = 3(x + 1)² - 2

Step 2: Find Standard Form

  1. Expand by FOILing: f(x) = 3(x² + 2x + 1) - 2
  2. Distribute 3: f(x) = 3x² + 6x + 3 - 2
  3. Combine like terms (constants): f(x) = 3x² + 6x + 1
User Unxnut
by
5.6k points